Norse stories - Hull, Robert (Wayland, Hove, 1993)
Norse Stories," retold by Robert Hull, published in 1993. This work is part of the "Tales from Around the World" series and offers a collection of Norse myths and legends, illustrated with both color and black-and-white artwork throughout. The book aims to introduce readers to the rich tapestry of Norse mythology, featuring tales of gods, heroes, and mythical creatures from ancient Scandinavian culture. It's designed to be accessible to a younger audience, making it suitable for educational purposes or as an introduction to Norse myths for children.